Isolation of antibiotic resistant Klebsiella pneumoniae from students with Urinary infections at a Tertiary Institution, Southwest Nigeria - C. O. , Anidiobu; A.O., Ajayi; M. A., Fowora; O. P. , Adejoh (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
The antibiotic resistance of urinary pathogens has been varying over the period of years, in healthcare-associated infections. The study provided the current isolation of antibiotic resistant Klebsiella pneumoniae from students with UTI at a Tertiary Institution, Southwest Nigeria. In the study, 200 clean midstream urine samples were collected and studied using standard microbiological techniques. Information for the factors associated with UTIs was obtained using questionnaires. An agar disc diffusion technique was used to test for antibiotic susceptibility. The chi-square test was used to express associations among descriptive variables of UTI. The study revealed that Klebsiella pneumoniae strains showed a low prevalence of UTI with 47(23.5%). The study showed females are more susceptible to UTIs than males. The age-wise distribution shows that the incidence is more common in age bracket 21 to 30 years. The Klebsiella pneumoniae strains were most susceptible to imipenem 40(85.1%), meropenem 33(70.2%), ceftazidime 32(68.1%), and cefexime 25(53.2%) as compare to amoxicillin-clavulanate 43(91.5%), ampiclox 30(68.8%), cotrimoxazole 37(78.7%) and tetracycline 24(51.1%) with high resistance rate. K. pneumoniae shown resistance to 9 different antibiotics with multiple antibiotic-resistance index of 0.6. Appropriate diagnosis and management of UTI are aimed at treating the acute occurrence as well as preventing recurrences of this infection.